Upaya Meningkatkan Hasil Belajar PAI Siswa melalui Penggunaan Media Gambar di kelas IV SDN 15 Sitiung Tahun Pelajaran 2021/2022: Efforts to Improve Student PAI Learning Outcomes through the Use of Image Media in grade IV SDN 15 Sitiung For the 2021/2022 Academic Year - maryulis maryulis (Perkumpulan Doktor Indonesia Maju (PDIM), 2022)
This research is the development of learning methods and strategies. The method in this study is a class action research method, which is a study that was developed jointly for researchers and decision makers about variables that are manipulated and can be used to make improvements. To make PAI and BP learning plans with the clean and healthy theme using image media, researchers followed the steps of image media and used learning methods to create fun learning activities so that they could improve student learning outcomes. In the implementation of learning with a clean is healthy theme, it must be based on learning plans that are prepared using picture media which are carried out in cycles I and II. it can be seen from the learning outcomes of the second cycle which is higher than the learning outcomes of the first cycle, which is 70.5 increased to 86.7. PAI and BP learning with the theme clean is healthy